PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA LAGU TERHADAP KETERAMPILAN MENULIS TEKS PUISI SISWA KELAS X SMA NEGERI 3 PAYAKUMBUH - Wati, Seprina; Asri, Yasnur; Nursaid, Nursaid (Universitas Negeri Padang, 2018)
ABSTRACT The purpose of this study is to explain the influence of discovery learning model assisted by song media to the skills of writing poetry text class X students SMA Negeri 3 Payakumbuh. This type of research is quantitative research with One Group Pretest and Posstest Design. Total population of 317 students. The sample in this study were students of grade X.3 SMA Negeri 3 Payakumbuh as many as 34 students determined by using purposive sampling technique. The data of this research is the result of the skill of writing poetry writing skill of class X student of SMA Negeri 3 Payakumbuh before and after using the discovery learning model with by song media. The results of the research are: First, the skill of writing poetry text of the students before using the model of discovery learning with the song media obtained an average score of 50.61. Second, the skill of writing poetry text of the students after using the discovery learning model of media auxiliary obtained an average score of 75,74. Third, based on the t-test, the alternative hypothesis (H1) is received at a significant level of 95% and degrees of freedom (dk) = n - 1 tcount> ttable (8,97> 1.70). Kata kunci: discovery learning, media lagu, keterampilan menulis, teks puisi